2015
DOI: 10.17265/2161-6256/2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunomodulatory Activity of the Herbals Formula Viranur, Turmeric (Curcuma heyneana Val.) and Phyllanthus (Phyllanthus niruri L.) in Layer Chicken Vaccinated with Avian Influenza

Abstract: Abstract:The aim of this research was to know the effect of herbal as immunomodulator on chicken layer vaccinated with avian influenza. A total of 60 chickens were alloted into three treatment groups: control group (KA), group KB and group KC, with 20 chicken each group. All the chickens were vaccinated with Newcastle disease (ND) in the age of one week, and a week later they were vaccinated with avian influenza (AI). The chickens in group KB were drunken with herbal solution containing of 5 g turmeric (Curcum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Hydroethanolic root extract at a dose of 400 mg/kg induced the highest spleen index (5.359 ± 0.174). The increase in organ index might also be due to the stimulatory effect of treatment on proliferation and differentiation of bone marrow stem cells that migrate to and settle within the organ for interaction with the incoming antigen, thereby increasing the mass of the organ [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hydroethanolic root extract at a dose of 400 mg/kg induced the highest spleen index (5.359 ± 0.174). The increase in organ index might also be due to the stimulatory effect of treatment on proliferation and differentiation of bone marrow stem cells that migrate to and settle within the organ for interaction with the incoming antigen, thereby increasing the mass of the organ [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Penentuan indeks berat organ limfoid seperti bursa Fabricius, timus, dan limpa dilakukan dengan menimbang masing-masing berat badan, berat organ limfoid, bursa Fabricius timus, dan limpa seperti dilansir (Hartati, et al, 2015) sebagai berikut: dimana: Bobot organ limfoid = bobot tiap organ limfoid Bobot Ayam = bobot tiap ayam…”
Section: Pemeriksaan Indeks Berat Organ Limfoidunclassified
“…Sebagai perbandingan, organ timus kontrol normal menunjukkan korteks timus tampak limfosit tersusun lebih padat dan tidak terlihat vakuolisasi(Gambar 8). Faktor kedua adalah imunomodulator emberian imunomodulator pada ayam yang telah di vaksinasi menunjukkan kepadatan limfosit tinggi pada organ limfoid dan meningkatkan bobot organ limfoid (Hartati et al, 2015). Indeks berat organ limfoid pada ayam omphalitis lebih rendah dibandingkan ayam sehat karena terjadi kematian atau kerusakan sejumlah limfosit pada folikel.…”
Section: Secara Histopatologi Organ Limfoidunclassified
“…All groups were challenged with H9N2 Avian Influenza virus, and the treatment group showed mild clinical symptoms, the lowest viral shedding and higher titer than the control group. Research conducted by Hartati et al [3] showed that giving curcumin in layer chicken feed stimulates lymphocyte activity. In the histopathological picture of the bursa fabricius, there was an increased number of lymphocytes in the lymphoid follicles and the thymus were also seen in widening of the cortex compared to the medulla.…”
Section: Introductionmentioning
confidence: 99%